Planting a Seed of Experience – Long Term Effects of a Co-curricular Ecogarden-Based Program in Higher Education in Hong Kong - Cheang, Chi-Chiu; Ng, Wai-Ki; Wong, Yuen-Sam Diana; Li, Wai-Chin; Tsoi, Kwok-Ho (Frontiers in Psychology, 2021)
This paper reports on the long-term effectiveness of a non-formal co-curricular educational program based on a campus ecogarden at a Hong Kong university in developing pro-sustainability awareness, attitudes and behavior among undergraduate students. This service-based, nature-based experiential learning program, termed the Ecogarden Farmer and Biodiversity Surveyor, has been running at the university since 2015. The program is divided into two consecutive phases: a training phase comprising various learning activities and a successive internship phase consisting of the all-round practical tasks involved in managing the garden. A retrospective evaluation of the program using phenomenographic approach and content analysis was adopted to reveal the diversity of students’ learning experience, as the indicators of the success of the program. Of 112 participants from 4 cohorts, 32 completed online questionnaires, and semi-structured interviews were successfully conducted with twelve participants, three from each of the four cohorts. The results indicated that the program’s outcomes could be categorized into five themes. Most outcomes fit into the theme ‘an increase in knowledge and skill level,’ followed by ‘rise in environmental awareness,’‘facilitation of personal growth,’ and ‘enhancement of career development.’ Many structural experiences revealed may suggest the success of the program. The longer the participants had participated in the program, the more in-depth and diversified reflection of the senior participants relating to personal development were mentioned. This study provides critical insights into the validity of retrospective program evaluation for assessing the long-term impact of EfS programs by introducing a cross-sectional study of different cohorts as a serial time-point sampling strategy.